Combining native and 'omics' mass spectrometry to identify endogenous ligands bound to membrane proteins - Gault, J; Liko, I; Landreh, M; Shutinm, D; Bolla, JR; Jefferies, D; Agasid, M; Yen, H-Y; Ladds, MJGW; Lane, DP; Khalid, S; Mullen, C; et al. (Springer Nature, 2020)
Ligands bound to protein assemblies provide critical information for function, yet are often difficult to capture and define. Here we develop a top-down method, 'nativeomics', unifying 'omics' (lipidomics, proteomics, metabolomics) analysis with native mass spectrometry to identify ligands bound to membrane protein assemblies. By maintaining the link between proteins and ligands, we define the lipidome/metabolome in contact with membrane porins and a mitochondrial translocator to discover potential regulators of protein function.